(untitled) (Nonlinear Studies, 2022)
In this paper, we intend to estimate the multifractal Hausdorff and the packing dimensions of product measures. The results in this paper establish the connections with various multifractal dimensions of measures on R^n, and generalize many known results about Hausdorff and packing dimensions of measures.